Corporate Governance Mechanism, Political Connection, and Accounting Conservatism: Evidence from Indonesia - Hendy Satria; Djoko Suhardjanto; Wahyu Widarjo; Setianingtyas Honggowati; Kusumaningdiah Retno Setiorini (Migration Letters, 2023)
This study aims to see the effect of corporate governance mechanisms, political connections, and accounting conservatism in Indonesia, using the moderating variable firm size. The samples used in this study amounted to 137 manufacturing companies for four years from 2019 to 2022, with 548 data. The results of this study indicate that all hypotheses are accepted. The independent commissioner, audit committee, and institutional ownership variables positively affect while political connections and firm size hurt accounting conservatism. Furthermore, the moderating variable’s measurement shows that the two equations show that firm size strengthens the relationship between corporate governance mechanisms and strengthens the relationship of political connections to accounting conservatism.